The Development Process of Higher Order Thinking Skills Based Poetry Text Assessment Tools on VIII Grade Students of Junior High School Brigjend Katamso II Medan - Sihombing, Erlina; Solin, Mutsyuhito; Gafari, M. Oky Fardian (BIRCU, 2019)
This study is aimed describe the process of developing higher order thinking skills based poetry text assessment tools. Students need to be trained in their thinking skills by giving students the type of Higher Order Thinking Skills (HOTS) that can be used to improve students' thinking skills. This research was conducted in Junior High School Brigjend Katamso II Medan. The result shows that Preliminary studies were research and gathering preliminary information, namely needs analysis. The needs analysis in this research development began by distributing questionnaires to the needs of eighth grade students of Junior High School Brigjen Katamso II Medan, amounted to 35 students and 2 Indonesian language teachers of Junior High School Brigjen Katamso II Medan. The results of the needs analysis were as follows: That 100% of the teachers stated that they knew the assessment tools and 70% knew the steps in preparing the assessment tools. However, only 0% of teachers test their assessment tools before use so that 100% of teachers need a valid, effective and practical assessment tool.